Sigit, Kajian Penerapan Sistem Iinformasi Akademik IBiI Berdasarkan Pendekatan TAM - Humdiana Roelly S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2012)
Growth of Information changing each;every moment completely quickly and online have knocked over the education world, so that the information circulating more and more and complect. Information system of Academic represent appliance for the consolidation usher requirement of requirement in process learn to teach and the important medium and support effectiveness of study in campus world. Process infrastructure renewal from conventional toward more modern start applied in IBII in the early the new semester 2004 2005. Becoming one of requirement of standard of gift information system of effective akademic if medium used by more acceptable This research entitle " Study of Applying of System of Iinformasi Akademik IBII of Pursuant to Approach TAM", studying Factors of what interaction and have an effect on to storey;level of technological acceptance specially SIA Akademic to all lectures, student and civitas akademic in IBII. Model used to know acceptance of Information System this Akademik IBII is model TAM ( Technology Acceptance Model) and use statistical test by SEM ( Structural Equation modelling) hence software Amos V16.0. In detail model TAM explain acceptance of TI with certain dimension which can influence technological acceptance by consumer. Model this place factor of attitude and every behavior of consumer by using two especial variable that is benefit ( usefulness) and use amenity ( easy of use). Anticipated by acceptance of software of System of this Iinformasi Akademik IBII is also influenced by other;dissimilar factor for example : variable of Attitude Toward Using ( ATU) Or attitude to use, variable of Intention to Use ( ITU) Or intention to use and variable of Actual Usage Behavior ( AUB) Or use behavior.